Avaliação da relação entre os instrumentos de avaliação formativa e somativa utilizados em um curso de medicina - Pedroso, João Paulo de Lima (2018)
Student evaluation is one of the challenges that the faculty must face. It is desirable to evaluate in an integral way, in which, knowledge, skills and attitudes are the goals of the process. Especially. In medical Courses The Student's formative evaluations have been employed, but in the literature it is not clear whether these are associated with the summation Evaluations. This work was for the general purpose to analyze whether the evaluation process and its formative evaluation tool used during the UNIFEV tutorials sessions correlates with the Student's summation assessment and as specific objectives to carry out a study Of the results obtained in the application of the instruments of evaluation formative in the second, fourth, sixth and eighth periods held during the tutorials sessions of the course of medicine at UNIFEV. 7155 evaluation Instruments of 209 students of the second, fourth, sixth and eighth periods of the medical course of the University Center of Votuporanga (UNIFEV) were evaluated using active methodologies in the development of their curriculum. The instruments were applied in the tutoring sessions in three moments: opening, intermediate and Closing. From these instruments a note was withdrawn, ranging from zero to Ten. The instruments were analyzed within the period itself and in relation to the other PERIODS. Correlations were also made between the formative evaluations and the bimonthly monthly note of the student carried out through the sum of the formative evaluation of three weight with the summation assessment composed of multiple choice questions with four Possible alternatives and essay issues carried out at the end of each bimaster. In the analyzed data, it was found that the formal opening, intermediate and closing evaluations varied significantly over the weeks, but the average obtained by the student was always very close to Ten. The analysis between the periods also showed that same uniformity. The analysis of the results showed the absence of statistical correlation or even negative correlations between the two methods of Evaluation. It was concluded that there is a homogeneity in the formative evaluations between the tutors of the same series and of the Course. Despite the lack of correlation, the benefits of the formative evaluations in producing attitudinal improvement in the student seem to be evident